The effectiveness of infrastrure related expanded public works programmes in reducing poverty : a case of Lepelle Nkumpi Municipality in Limpopo Province - Mabotja, Sello Logan (My University, 2024)
Infrastructure related Expanded Public Work Programmes (EPWPs) are widely implemented by the South African government as one of a labour intensity initiative providing temporary employment and income transfer to unemployed people in an effort to reduce poverty. The infrastructure-related EPWP, which aims to provide beneficiaries with training and skill development as well as build affordable and highquality assets, has been implemented by the Lepelle-Nkumpi Local Municipality and the Limpopo Department of Public Works, Roads, and Infrastructure (LDPWRI). This study assessed the effectiveness of infrastructure-related EPWP in reducing poverty in rural communities in Limpopo province's Lepelle-Nkumpi Municipality. The study used a qualitative method design with purposive sampling. The Capability Approach and the Sustainable Livelihoods Framework were used as the conceptual framework for this study. The narratives were derived from in-depth interviews and focus groups with the Lepelle-Nkumpi Local Municipality and LDPWRI officials and infrastructure related EPWP beneficiaries. The study found that while the EPWP has improved beneficiaries' livelihoods by increasing their income and household assets, a greater emphasis on skill development and training is needed to ensure that beneficiaries are employable and can start their own businesses or find sustainable employment, thereby reducing poverty.
Thesis (M.Dev. (Planning and Management)) -- University of Limpopo, 2024
Keywords: Infrastructure relate EPWP; Poverty; Skill development; Sustainable jobs; Sustainable livelihoods; Public service employment -- South Africa -- Limpopo; Economic development -- South Africa -- Limpopo; Poverty -- South Africa -- Limpopo; Sustainable development -- South Africa -- Limpopo